2021
DOI: 10.1111/raq.12605
|View full text |Cite
|
Sign up to set email alerts
|

Acquired tetracycline resistance genes by transposons and virulence factors in enterococci recovered from overland and aquatic animals: A systematic review

Abstract: Enterococci possess a high propensity to spread their resistance genes between intra-and inter-species via mobile genetic elements. Potential reservoirs for acquiring antibiotic resistance genes by commensal and environmental bacteria, including enterococci, have raised significant public health concerns over recent decades. This concern is further complicated by the rampant use of tetracyclines in aquaculture and animals for therapeutic and chemoprophylactic purposes. This systematic review was conducted to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 56 publications
(221 reference statements)
0
5
0
Order By: Relevance
“…This systematic review strictly followed the preferred reporting items for systematic reviews [19][20][21]. This systematic literature review obtained IRB approval (No.…”
Section: Methodsmentioning
confidence: 99%
“…This systematic review strictly followed the preferred reporting items for systematic reviews [19][20][21]. This systematic literature review obtained IRB approval (No.…”
Section: Methodsmentioning
confidence: 99%
“…Surprisingly, tetracycline resistance genes in particular were found to be associated with mobile genetic elements such as the tetA (H)-carrying plasmid [ 68 ] and tetR and tetC encoded by Tn 10 [ 8 ]. Tetracycline is a broad-spectrum antibiotic and is widely used in human and veterinary medicine to treat bacterial infections due to its low price and limited side effects [ 98 100 ]. Moreover it has been added to animal feed as a growth promoter [ 98 , 99 ].…”
Section: Antibiotic Susceptibility Of W Chitiniclasticamentioning
confidence: 99%
“…Tetracycline is a broad-spectrum antibiotic and is widely used in human and veterinary medicine to treat bacterial infections due to its low price and limited side effects [ 98 100 ]. Moreover it has been added to animal feed as a growth promoter [ 98 , 99 ]. A recent systematic review showed that there is still continuous contamination with tetracyclines in both aquatic and terrestrial animals, leading to selection pressure on antibiotic-resistant bacteria [ 98 ] and by that to an alarming rise in antibiotic resistance to tetracycline [ 101 ].…”
Section: Antibiotic Susceptibility Of W Chitiniclasticamentioning
confidence: 99%
See 1 more Smart Citation
“…Improper food preparation and storage and poor personal hygiene are among the main contributing factors [ 13 ]. Moreover, the infectious agents of food poisoning might originate from humans, animals, or animal products [ 14 , 15 ]. Considering children and young adolescents are more likely to be involved in risky or unhygienic food handling practices and would exclusively spend their mealtime in school canteens, the risk of food poisoning is extremely high [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%